Normal Functions over Locally Symmetric Varieties - Keast, R.; Kerr, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We classify the irreducible Hermitian real variations of Hodge structure admitting an infinitesimal normal function, and draw conclusions for cycle-class maps on families of abelian varieties with a given Mumford-Tate group.